The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1007/s12544-017-0276-2
|View full text |Cite
|
Sign up to set email alerts
|

Headway distribution models of two-lane roads under mixed traffic conditions: a case study from India

Abstract: Introduction The time headway of vehicles is of fundamental importance in traffic engineering applications like capacity, levelof-service and safety studies. Further, the performance of traffic simulation depends on inputs into the simulation process and 'accurate vehicle generation' is critical in this context. Thus, it is important to define headway distribution pattern for the purpose of analyzing traffic and subsequently, taking infrastructure related decisions. In so far, majority of the researches on thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…The table shows that the log-normal distribution has the least estimation error value. This is consistent with the literature which reported that the log-normal distribution offers a close fit to the intervehicle distance [32]- [34]. Hence, the distribution of the inter-vehicular distances is given by…”
Section: Data Processing Results and Discussionsupporting
confidence: 91%
“…The table shows that the log-normal distribution has the least estimation error value. This is consistent with the literature which reported that the log-normal distribution offers a close fit to the intervehicle distance [32]- [34]. Hence, the distribution of the inter-vehicular distances is given by…”
Section: Data Processing Results and Discussionsupporting
confidence: 91%
“…Step 2: modify the weight of the single model matched with the new pixel, dw � α • (1 − w i (x, y, t − 1)), and the weight increment is expressed as follows [15,16]:…”
Section: Updating the Parameters And Performing Foreground Detectionmentioning
confidence: 99%
“…Jang [19] reported four models for various states of traffic flow on suburban arterial roads including the Johnson system bounded model, the Johnson system unbounded model, the log-logistic model, and the log-normal model [19]. Roy and Saha [20] concluded that the log-logistic distribution is an appropriate choice for moderate traffic flow, but the performance of Pearson 5 is good under congestion [20]. However, the situation near the stop line is very different where the traffic flow is interrupted and the time headway is influenced by signal control [21].…”
Section: Studies Of Time Headwaymentioning
confidence: 99%